2017
DOI: 10.2166/ws.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of a skimming wall on controlling the sediment entrance at lateral intakes

Abstract: Sediment entering lateral intakes depends on the flow pattern at the intake entrance. Using a structure in front of the intake entrance can change this pattern and as a result the entering sediment. One of the effective method to change the pattern and manage sediment entering a lateral intake is to use a skimming wall. The removal of sediments from the intake entrance using a skimming wall led to reduction of sediment volume at the intake. To guide flow into the diversion canal and increase skimming wall perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…To make a comparison between the results of the present study and comparable works, the results and findings of Barkdoll et al (1999), Raudkivi (1993), Hassanpour (2007), and Moradinejad et al (2017) were studied. Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To make a comparison between the results of the present study and comparable works, the results and findings of Barkdoll et al (1999), Raudkivi (1993), Hassanpour (2007), and Moradinejad et al (2017) were studied. Fig.…”
Section: Discussionmentioning
confidence: 95%
“…iments for a single Froude number, but he focused on a range of 0.4 to 0.6 for the Froude number. Moradinejad (2017) assumed that the value of varies Q R between 0.1 to 0.2 and that an increase Q R in leads an increase in the ratio of the deviated sediment to the intake. He showed that a 14% increase in a stream's Froude number causes an increase in the ratio of the inlet sediment ratio to the intake up to 118%.…”
Section: Tab 4 Statistical Information On the Relation With For Different Froude Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediments were weighted after 30 min. Like study Moradinejad et al (2017), to control sediments movement as bed load in selected discharge range, Shields diagram was used. The experimental conditions were as follows: minimum discharge: 0.025 m 3 /s, slope of moving bed: 0.002, flow depth: 4.6 cm, hydraulic diameter: 0.0452 m, shear velocity: 0.0298 m/s, boundary Reynolds (Re*): 25.48 and Shields parameter (θ): 0.0548.…”
Section: Methodsmentioning
confidence: 99%
“…Spur dikes are simple hydraulic structures which are used to organize river bends or their straight line. They are used to control erosion and protect river banks and are of the deviation type (Moradinejad et al 2017;Daneshfaraz et al 2015). This structure causes changes in the flow pattern due to the reduction in the flow separation at the bottom.…”
Section: Introductionmentioning
confidence: 99%